Emerging modes of PINK1 signaling: another task for MARK2 - Matenia, Dorthe; Mandelkow, Eva M. (Frontiers in Molecular Neuroscience, 2014)
PTEN-induced kinase 1 (PINK1) acts at multiple levels to promote mitochondrial health, including regulatory influence on ATP-synthesis, protein quality control, apoptosis, mitochondrial transport and destiny. PINK1 mutations are linked to Parkinson disease and mostly result in loss of kinase activity. But the molecular events responsible for neuronal death as well as the physiological targets and regulators of PINK1 are still a matter of debate. This review highlights the recent progress evolving the cellular functions of the cytosolic pool of PINK1 in mitochondrial trafficking and neuronal differentiation. Regulation of PINK1 signaling occurs by mitochondrial processing to truncated forms of PINK1, differentially targeted to several subcellular compartments. The first identified activating kinase of PINK1 is MAP/microtubule affinity regulating kinase 2 (MARK2), which phosphorylates T313, a frequent mutation site linked to PD. Kinases of the MARK2 family perform diverse functions in neuronal polarity, transport, migration, and neurodegeneration such as Alzheimer disease. This new protein kinase signaling axis might provide a link between neurodegenerative processes in Alzheimer and Parkinson diseases and opens novel possibilities in targeting pathological signaling processes.